2022
DOI: 10.3389/fphar.2022.926802
|View full text |Cite
|
Sign up to set email alerts
|

Lactylation may be a Novel Posttranslational Modification in Inflammation in Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: Perinatal hypoxia-ischemia remains the most common cause of acute neonatal brain injury and is associated with a high death rate and long-term neurological abnormalities such as memory and cognitive deficits and dyskinesia. Hypoxia-ischemia triggers an inflammatory cascade in the brain that is amplified by the activation of immune cells and the influx of peripheral immune cells into the brain parenchyma in response to cellular injury. Thus, acute cerebral hypoxic-ischemic inflammation is a major contributor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…High levels of lactate and pyruvate can increase the production of reactive oxygen species (ROS) and inflammatory mediators, damage the blood–brain barrier (BBB), and lead to edema. These changes eventually result in sustained neuronal damage within 6–48 h post-injury [ 13 , 21 , 50 , 51 ]. Consistent with this, we also observed elevated levels of pyruvate and lactate in the hippocampal tissue of acute HI mice, indicating a greater reliance on glycolysis by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of lactate and pyruvate can increase the production of reactive oxygen species (ROS) and inflammatory mediators, damage the blood–brain barrier (BBB), and lead to edema. These changes eventually result in sustained neuronal damage within 6–48 h post-injury [ 13 , 21 , 50 , 51 ]. Consistent with this, we also observed elevated levels of pyruvate and lactate in the hippocampal tissue of acute HI mice, indicating a greater reliance on glycolysis by the cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that lactate reduces M1 macrophage activation and promotes M2 macrophage polarization by modifying histones in the inflammatory response ( Zhang et al, 2019 ; Ivashkiv, 2020 ). Further studies on histone lactation may lead to new therapeutic targets for OA treatment and strategies for resolving inflammation ( Zhou et al, 2022 ). The activity and expression of LDH are significantly increased in primary chondrocytes treated with IL-1β.…”
Section: Ldhamentioning
confidence: 99%
“…The pathophysiology of HIE is complex and remains poorly understood. However, dysfunction of mitochondrial and cerebral glucose metabolism has been identified as a key factor . In mitochondria, KBs can act as alternative substrates for ATP production .…”
Section: Ketosis and Cerebral Metabolismmentioning
confidence: 99%
“…However, dysfunction of mitochondrial and cerebral glucose metabolism has been identified as a key factor. 27 In mitochondria, KBs can act as alternative substrates for ATP production. 28 In addition, free fatty acids are converted to KBs, which are then converted to acetyl-CoA and enter the Krebs cycle.…”
Section: ■ Ketosis and Cerebral Metabolismmentioning
confidence: 99%